Fabrication, Characterization And Humidity Sensing Properties Of Radio Frequency Magnetron Sputtered Calcium Copper Titanate (CCTO) Thin Film. - Ahmadipour, Mohsen (2018)
Resistance-type humidity sensor based on CCTO thin films which are capable of sensing of humidity in the range of 30%-90% and short period of time have been successfully fabricated by using radio frequency (RF) magnetron sputtering technique. The CCTO thin film humidity sensor based-on resistance measurement has never been reported before. The aim of this study is to fabricate a humidity sensor with small size and simple structure in order to reduce the fabrication cost, to enhance of CCTO thin film humidity sensing properties, and finally to prove the great potential of CCTO as a humidity sensing application. CCTO thin film with 200 nm, 400 nm, and 600 nm thicknesses were deposited on alumina (Al2O3) substrates, respectively and physically analyzed by field emission scanning electron microscopy which is connected with energy dispersive X-ray spectroscopy (FESEM-EDAX), X ray diffraction (XRD) and atomic force microscopy (AFM) in order to understand their microstructure and morphology. Prior to CCTO deposition, the fabrication process was assisted by thermal evaporator to prepare the highly conductive interdigitated silver electrode. The CCTO thin film humidity sensor electrically tested in different relative humidity (RH) (30% to 90%) at ambient temperature. Results exhibited that resistance of all samples decreased with increasing the CCTO thin film thickness and also upon exposure to humidity. In addition, a quick response time i.e., approximately less than 1 min was observed for both CCTO thin films. For device based on 200 nm CCTO thin film, high humidity sensing properties (Response time = 10 s, Recovery time = 450 s, Sensitivity = 75.6 %) was observed upon exposure to humidity. When the measurements were repeated after a month, the CCTO thin film showed remarkable stability. The possible mechanism between humidity and CCTO thin film was proposed whereby the humidity sensing process is correlated to adsorption and desorption water on the films surface at low RH, water molecule will not cover the surface completely and can only chemisorb on the available site of the CCTO surface. Furthermore, water adsorbing will not provide electrons to sensing layers and will significantly lower the sensing properties of CCTO thin film humidity sensor. At high RH, the larger content of water is adsorbed, so the density of charge carrier becomes higher and hence the sensing properties increases. Thus, the performance of the CCTO thin film electrical properties achieved the requirement for good humidity sensor. Moreover, its ability to detect relative humidity in range 30%-90% qualified this CCTO thin film as a very promising potential to be applied as a practical and high performance humidity sensor in the near future.